Novel light-driven functional AgNPs induce cancer death at extra low concentrations - Ulviye Bunyatova (Nature Portfolio, 2021)
Abstract The current study is aimed at preparing light-driven novel functional AgNPs- bio-hydrogel and evaluating anticancer potency against human melanoma cells. With an average size of 16–18 nm, the hydrogel nano-silver particle composite (AgNPs@C_MA_O) was synthesized using a soft white LED approach and analyzed by UV–Vis, DLS, FTIR, X-ray, SEM–EDX and TEM techniques. The anticancer activity of the obtained novel functionalized AgNPs@C_MA_O was tested in-vitro in the A375 melanoma cell line. Dose–response analysis showed that AgNPs at 0.01 mg/mL and 0.005 mg/mL doses reduced the viability of A375 cells by 50% at 24 and 48-h time-points, respectively. A375 cells treated with AgNPs@C_MA_O for 24 h at IC50 displayed abnormal morphology such as detachment edges and feet, shrinkage, membrane damage, and the loss of contact with adjacent cells. Our work is the first study showing that non-ionizing radiation mediated biofunctionalized AgNPs have an anti-tumoral effect at such a low concentration of 0.01 mg/mL. Our approach of using harmless wLED increased synergy between soft biopolymer compounds and AgNPs, and enhanced anticancer efficiency of the AgNPs@C_MA_O biohydrogel. Ultimately, the AgNPs accessed through the use of the wLED approach in colloidal syntheses can open new applications and combinatorial advanced cancer treatments and diagnostics.